2009
DOI: 10.1299/jbse.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Tensile Properties of Thoracic Aortic Aneurysm Tissues

Abstract: Mechanical properties of human aortic aneurysm tissues were measured with a biaxial tensile tester. Fifteen-mm-square specimens were obtained from thoracic aortic aneurysms of various origins and from undilated aortas adjacent to the aneurysms during aneurysmectomy, and were stored frozen until the measurement. Each specimen was stretched biaxially in physiological saline at room temperature at the rate of ~0.2 mm/sec. Although the ordered displacement was set equal for both directions, real strain applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
(21 reference statements)
1
40
0
Order By: Relevance
“…About the freezing effects in porcine thoracic aorta samples, Matsumoto et al (2009) showed that the mechanical properties were similar for samples stored at −23°C in comparison to fresh specimens at 37°C. Before the OCT acquisition, the tissue was placed into an osmotically active solution of 85% (v/v) PG in PBS, at 37°C for 2 h (Lomas et al, 2003).…”
Section: Materials and Methods Sample Preparationmentioning
confidence: 97%
“…About the freezing effects in porcine thoracic aorta samples, Matsumoto et al (2009) showed that the mechanical properties were similar for samples stored at −23°C in comparison to fresh specimens at 37°C. Before the OCT acquisition, the tissue was placed into an osmotically active solution of 85% (v/v) PG in PBS, at 37°C for 2 h (Lomas et al, 2003).…”
Section: Materials and Methods Sample Preparationmentioning
confidence: 97%
“…The stress-strain curves converted to the equibiaxial stretch condition, and the anisotropic index, the difference in stiffness between circumferential and longitudinal directions divided by the average stiffness, was calculated for each sample (Matsumoto et al, 2009). …”
Section: Constitutive Modelingmentioning
confidence: 99%
“…In particular, some studies move from the presentation of new tools in imaging analysis to evidence possible alterations in the morphology and in the micro-structure of the diseased aortic tissues [26,27]. Other studies focus on the use of mechanical tests (uniaxial and biaxial tensile tests) to evaluate and compare mechanical properties of both healthy and diseased tissues [28][29][30][31][32][33] and, at the same time, to investigate factors which can influence tissue properties like location and orientation [23,[34][35][36][37], patient age [30,38,39], patient sex [39,40], and presence of concomitant pathologies [25,33,36,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%